Mitochondrial Dynamics in Adult Cardiomyocytes and Heart Diseases - Li, Anqi; Gao, Meng; Jiang, Wenting; Qin, Yuan; Gong, Guohua (Frontiers in Cell and Developmental Biology, 2020)
Mitochondria are the powerhouse organelle of cells that participates in ATP generation, calcium homeostasis, oxidative stress response, apoptosis. Thus, timely maintain the function of mitochondria is critical for cellular functions. As highly dynamic organelles, the function of mitochondria is dynamically regulated by their fusion and fission in many cell types, which regulate mitochondrial morphology, number, distribution, metabolism, and biogenesis in cells. As a particular cell, mature rod cardiomyocyte with thousands of end-to-end contacted spheroid mitochondria, which limits the movement of mitochondria and thus hinder the research motivation of mitochondrial dynamics in adult cardiac. In this review, we discuss the most recent progress on the mitochondrial dynamics in mature (adult) cardiomyocytes.